An overview of risk investment in the transnational illegal wildlife trade from stakeholder perspectives. Issue 2 (14th October 2020) - Brown, Amber O.; Frankham, Greta J.; Bond, Luke; Stuart, Barbara H.; Johnson, Rebecca N.; Ueland, Maiken
Abstract: The illegal wildlife trade (IWT) is a lucrative, clandestine trade that endangers animal welfare, damages native biodiversity and undermines the rule of law. Despite enhanced law enforcement focus and increased litigation, the illicit trade of wildlife and wildlife products has continued to flourish. The increase in the IWT can be attributed to a lack of identifiable relationships, risk functions and reward systems specific to each stakeholder in this illicit market. The increase in the IWT indicates that domestic and international regulations are not effective in their intent of preventing the illegal trade of various wildlife species. Without a clear understanding of stakeholder relationships, resources will continue to be wasted on ineffective prevention and detection methods with regards to the IWT. Law enforcement strategies rely on identifying key stakeholders in the IWT as well as their perceived motivations, risks, and relationships. These definitions may provide further insight into the motivations driving these individuals participating in this illicit market and may contribute to more successful interventions. Stakeholders and their associated roles within the IWT have been defined to serve as a tool to understand the various risk/reward utility functions in global markets. This study provides a framework support for policy makers by establishing baseline risk/reward systems for each stakeholder which can be built upon as intelligence surrounding these stakeholders increases. This article is categorized under: Jurisprudence and Regulatory Oversight > Communication Across Science and Law Jurisprudence and Regulatory Oversight > Interdisciplinary Collaboration Abstract : Reflections on the importance of defining stakeholders in the illegal wildlife trade to aid in more effective enforcement and regulation.